Impact of Big-Five Personality on Job Stress of Staff: A Case Study of Regional Directorate of Health Services Office, Jaffna - Raveendran, T. (JUICE- 2012 University of Jaffna, 2012)
Despite the enormerous growth in research on personality due to the development of big five personality model, still there is inadequate research among the organizations in Jaffna context. This study attempts to fill the gap by exploring the effects of the personality traits on job stress. This study examined the “Big Five” personality dimensions in relation to Job Stress by surveying a sample of 38 staff at Regional Directorate of Health Services Office, Jaffna. The objective of this study was to examine the effects of personality variables (extraversion, conscientiousness, openness, agreeableness and neuroticism) on job stress among the staff working in the Regional Directorate of Health Services Office. The study was based on self reported questionnaire. The „Big Five‟ traits of personality were measured using Goldberg‟s (1999b) International Personality Item Pool (IPIP). Stress was assessed with Perceived Stress Scale (PSS-10) (Cohen, Kamarck and Mermelstein, 1983). The analysis of data included assessments of reliability, correlations and regression analysis. Analyses of responses revealed that conscientiousness and openness were found to have significant and negative impact on job stress. Neuroticism, on the other hand, had significant positive impact on job stress. This study gives an understanding of the influence of personality variables on job stress of employees. From the findings, the management of Regional Directorate of Health Services Office can consider the personality potentials of the staff and focus on the type of personality to be developed among the staff. In addition, during the interview process, top management can consider certain personality characteristics, specifically those who exhibit high conscientiousness and openness traits and low neuroticism. Given that there may be other personality factors that also affect and moderate job stress related outcomes, researchers interested in this area should try to explore these factors in future.
Keywords: Personality; Big-five Traits; Job Stress